In Vitro Clumping of Human Platelets by Dextran - Dhall, D. P; Matheson, N. A (Thrombosis and Haemostasis, 1968)
Platelet aggregation in vitro by dextrans of various molecular weights has been examined in platelet rich plasma and in suspensions of human platelets with a turbidi-metric method and microscopy. Addition of dextran to platelet rich plasma and platelet suspensions causes a biphasic effect on the optical density, consisting of an immediate decrease which seems independent of the molecular weight of the dextran and a delayed, time-dependent decrease influenced by it. Microscopically, platelet aggregation by dextran corresponds more closely to the delayed decrease. Aggregation of human platelets by dextran, for which stirring is necessary, is related to the final dextran concentration, is affected by the platelet population and is not spontaneously reversible. Platelet clumping by dextran is of particular interest since dextran has been shown to possess antithrombotic properties.